Mapeamento de QTL para resistência a Sporisorium scitamineum em população bi-parental de cana-de-açúcar - Silveira, Bianca Rocha (2016)
The sugarcane is a major global economic importance culture, especially for Brazil. The country is the largest producer of culture and its by-products, sugar and alcohol. The sugarcane has received attention for the generation of electricity. Since the importance of the sugar-energy sector, there is a need to increase agricultural production. This culture is exposed to various diseases caused by pathogens that impair the production of culture. Coal disease is one of them, caused by the fungus S. Scitamineum, making it less susceptible productive varieties and can cause loss of up to 100% of the plantation. More productive varieties with resistance to more diseases, obtained in less time are focused on breeding programs. The study aims to find microsatellite markers (SSR) associated with resistance of sugarcane to the fungus S. scitamineum. It used an F1 population (SP81-3250 RB925345 x) composed of 238 genotypes. Artificial inoculation of sugarcane stalks of the population through telia injection was made. The billets were kept in a greenhouse, and 25 were carried out between January and September 2014 for the first experiment and August 2015 to February 2016 for the experiment II, to identify the incidence of the disease. Molecular analysis and construction of linkage map were made by genotyping with SSR markers, which enabled the construction of linkage map with 128 brands linked, generating 49 linkage groups with a total length of 1297.68 cm. For data on the incidence of coal was used to calculate the area under the disease progress curve (AACPD), normalized to BLUPS values. The analysis allowed us to observe a population with more tolerant genotypes in experiment I and little disease in experiment II. In addition, it was noted that for the first experiment, the 10th to the 25th evaluation, the results were highly correlated, it was not repeated for the second trial. Experiment II showed low incidence in all genotypes of the population and patterns in the study. This incidence difference between the two experiments probably occurred by the difference in temperature conditions to which they were exposed, and the first experiment was set up in the summer with a starting temperature higher and the second trial began with mild temperatures and were increasing with time, the same occurs for the incidence of the disease. The association between phenotype and genotype was performed by analysis of variance, converted to LOD score. It was possible to verify an EST-SSR marker, SCB 370, which was significant (LOD> 3), explaining in 5% of the phenotypic variation for the experiment I.